2014
DOI: 10.1063/1.4872174
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of drop and bubble dynamics with soluble surfactant

Abstract: Numerical computations are presented to study the effect of soluble surfactant on the deformation and breakup of an axisymmetric drop or bubble stretched by an imposed linear strain flow in a viscous fluid. At the high values of bulk Peclet number Pe in typical fluid-surfactant systems, there is a thin transition layer near the interface in which the surfactant concentration varies rapidly. The large surfactant gradients are resolved using a fast and accurate "hybrid" numerical method that incorporates a separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In fact, there is a widespread belief that surfactant is a necessary element to produce tip streaming in unbounded extensional flows. Tip streaming has been described from simulations of such systems (Eggleton et al 2001;Booty & Siegel 2005;Bazhlekov et al 2006;Wang, Siegel & Booty 2014).…”
Section: Surfactant-covered Droplets In Linear Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is a widespread belief that surfactant is a necessary element to produce tip streaming in unbounded extensional flows. Tip streaming has been described from simulations of such systems (Eggleton et al 2001;Booty & Siegel 2005;Bazhlekov et al 2006;Wang, Siegel & Booty 2014).…”
Section: Surfactant-covered Droplets In Linear Flowsmentioning
confidence: 99%
“…The size of the ejected thread increases with the initial surfactant surface concentration. Wang et al (2014) studied the tip streaming numerically in a droplet covered with a soluble surfactant, placed in a uniaxial extension flow. They showed that the adsorption of a small amount of surfactant onto the interface produces tip streaming.…”
Section: Surfactant-covered Droplets In Linear Flowsmentioning
confidence: 99%
“…(i) Bi → 0, found when there is no desorption from the interface to the bulk, i.e. k d → 0 (Booty & Siegel 2010;Wang et al 2014). This condition is equivalent to setting the flux J b = 0 in (2.28) and (2.29);…”
Section: Governing Equations Within the Fluidsmentioning
confidence: 99%
“…A large part of past studies deal with the spreading of soluble liquids (mostly alcohols) on water, i.e., systems without cmc and micelles [38][39][40][41][42][43]. When solutions of soluble surfactants are considered, mostly numerical simulations have been done [44][45][46], whereas experimental studies often focused on transient behavior, especially on front propagation [47][48][49]. Moreover, experimental results were often collected for very thin films (less than 1 mm in thickness), adding complexities such as the occurrence of fingering instabilities [50,51].…”
Section: Introductionmentioning
confidence: 99%